2007
DOI: 10.1002/hed.20542
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 expression in medullary thyroid carcinoma

Abstract: COX-2 is expressed significantly in MTC including a larger area of staining and greater intensity than in nonmalignant thyroid tissue. These findings may have important treatment implications for the use of COX-2 inhibitors in patients with MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…In this study, cox‐2 expression was observed in 50% of MTCs and in only 13% of FTCs. The higher prevalence of cox‐2 expression in MTC is in agreement with reports in humans, where 26–41% of FTCs and 75–82% of MTCs have been shown to express cox‐2 . In a study investigating cox‐2 expression in canine invasive TCC of the urinary bladder, the percentage of positive tumor cells at diagnosis ranged from 1 to 22%, comparable to that found in our study .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, cox‐2 expression was observed in 50% of MTCs and in only 13% of FTCs. The higher prevalence of cox‐2 expression in MTC is in agreement with reports in humans, where 26–41% of FTCs and 75–82% of MTCs have been shown to express cox‐2 . In a study investigating cox‐2 expression in canine invasive TCC of the urinary bladder, the percentage of positive tumor cells at diagnosis ranged from 1 to 22%, comparable to that found in our study .…”
Section: Discussionsupporting
confidence: 92%
“…COX-2 expression has been explored in neuroendocrine tumours, including studies of the biological potential and therapeutic possibilities. It was widely expressed in up to 82% of medullary thyroid carcinoma, showing statistically significant up-regulation in comparison with benign thyroid tissue [113]. In phaeochromocytoma, COX-2 is associated with malignant behaviour and, along with lack of nm-23 and presence of galectin-3, can be applied to predict malignancy [114].…”
Section: Cox-2mentioning
confidence: 99%
“…The expression of COX-2 in MTC was evaluated in an immunohistochemical study by Popovtzer et al [95]. They evaluated tissue specimens of 22 patients with MTC and 15 control subjects with non-malignant thyroid tissue, concluding that COX-2 is overexpressed in the MTC tissue.…”
Section: Molecular Biology Of Mtc and The Ret Proto-oncogenementioning
confidence: 99%